Energy level alignment at the methylammonium lead iodide/copper phthalocyanine interface - Chen, Shi (2014)
The energy level alignment at the CH3NH3PbI3/copper phthalocyanine (CuPc) interface is investigated by X-ray photoelectron spectroscopy (XPS) and ultraviolet photoelectron spectroscopy (UPS). XPS reveal a 0.3 eV downward band bending in the CuPc film. UPS validate this finding and further reveal negligible interfacial dipole formation – verifying the viability of vacuum level alignment. The highest occupied molecular orbital of CuPc is found to be closer to the Fermi level than the valance band maximum of CH3NH3PbI3, facilitating hole transfer from CH3NH3PbI3 to CuPc. However, subsequent hole extraction from CuPc may be impeded by the downward band bending in the CuPc layer.